Digitaria clarkei (Paniceae, Panicoideae, Poaceae) a new species with paniculate synflorescence and D. costaricensis a new record from Mexico - Sánchez-Ken, J. Gabriel (Phytotaxa, 2017)
Digitaria clarkiae, a new species from the states of Guerrero, Morelos, and Puebla in México, is described and illustrated. The new species is compared to species of sect. Pennatae (D. arenicola, D. cognata and D. pubiflora) with so-called paniculate synflorescences, and to species of sect. Trichachne (e.g., D. patens), with which it shares an elongated rachilla between the glumes and the florets called the “stipe” and unequal spaces between the veins of the sterile lemma. Because the new species shares characteristics with both sections, its probable sectional affiliation based on morphological characters remains unclear, leaving it as incertae sedis in the genus. Digitaria costaricensis of section Debiles (Aequiglumae) is a new record from Veracruz, México.